Efektivitas Dinding Sandwich Panel dan Precast ACC Panel Terhadap Biaya dan Waktu - Kholis Hapsari; Ardia Tiara Rahmi; Delista Putri Deni (Kadiri University, 2023)
Project delays in construction development have a major impact, especially on costs. Projects that experience delays in implementation will require large costs. One of the delay factors is caused by material selection, especially for wall materials. Precast AAC Panel wall and sandwich panel walls are current wall material innovations, but both differ in material composition, implementation method, and price. This research aims to analyze the effectiveness of the two types of walls in terms of cost and time. The research will use objects from the 24-story Sudimaran Forestwalk apartment development in South Tangerang. The research method uses quantitative methods by making a cost budget plan obtained from data on work volume, productivity, and unit price of work. Next, analyze the duration of work from productivity data and work volume. The analysis results for the budget for work costs using precast AAC panel materials cost IDR 11,640,163,103, while sandwich panel walls are IDR 16,223,117,608. For comparison of implementation time, precast AAC panel walls are faster, with a work duration of 623 days, and sandwich panel walls 784 days. From these price results, AAC panel walls are 23% cheaper than sandwich panel walls. Due to the low strength, the sandwich panel walls are sometimes damaged during construction, resulting in longer construction times. The analysis results show that precast AAC panel walls are more recommended as the choice of wall type in terms of cost and implementation time.